Flexural capacity and stiffness of monolithic biaxial hollow slabs - Valivonis, Juozas; Jonaitis, Bronius; Zavalis, Robertas; Skuturna, Tomas; Šneideris, Arnoldas (Journal of Civil Engineering and Management, 2014)
The article presents a research on flexural behaviour of hollow monolithic reinforced concrete slabs. It focuses on the results of experimental investigation into full-size hollow reinforced concrete slabs and analyses their flexural capacity and stiffness. The self-weight of the slabs directly depends on the shape and number of hollows. An increase in the hollowness of a slab significantly reduces the load caused by self-weight. This allows increasing the estimated length of the slab under the same payload. An increase in the amount of hollows of the slab changes the stiffness of the slab cross-section that has a direct impact on slab deflection. Considering the shape of the slab cross-section, theoretical calculations of the flexural capacity and deflection of experimental slabs were made. The design of a new type of slabs and variations in different parameters of the slab experience difficulties in conducting a large amount of experimental tests. Therefore, the initial analysis may apply to numerical simulation. The paper describes the principles of designing a numerical model. The calculations were made using DIANA software. The stiffness and flexural capacity of the hollow slabs were established employing numerical simulation compared to the results of experimental investigations. The findings indicate that numerical simulation can be applied for analysing the stress state of the examined structures.